A Study of the Different Modes of Transmission of Borrelia burgdorferi by Ixodes ridnus - Monin, Robert; Gern, Lise; Aeschlimann, André (My University, 1989)
Only a small number of unfed Ixodes ricinus larvae collected in nature have been found to be infected by Borrelia burgdorferi (Bb). Therefore iransovarial transmission seems to be rare.
In contrast, an average of 30% of unfed nymphs and adults are infected. This finding shows that the ticks have become infected during an immature stage. It also provides an indication of the efficiency of the transstadial transmission.
The purpose of this study was to estimate the efficiency of the transovarian and transstadial transmissions. Different methods to infect the ricks in the laboratory were used.
Bb growth following to blood meal in unfed artificially infected females of I. ricinus was studied by a combination of the cryocut and direct imrnunofluorescence techniques. Some ticks (2/11) had spirochetes in their hemolymph 2 days after the beginning of the blood meal. Bb has been observed in the salivary glands of some ticks (6/51) and in the ovaries (5/ 51) from the third day of blood meal.
No spirochetes were detected in the rectal ampulla, so the possibility of transmission through spirochete-infected fecal material seems to be negligible.